Nutritional Status, Personal Hygiene and Health Seeking Behavior of the Workers of British American Tobacco Company, Dhaka, Bangladesh - Haque, Md. Jawadul; Awal, Md. Abdul; Rahman, Monowara; Sazzad, Jarin (Bangladesh Journal of Bioethics, 2017)
This cross sectional study was carried out among the workers of British American Tobacco Company, Dhaka with a view to explore their nutritional status, personal hygiene and health seeking behavior as because they are working on a tobacco processing company. The sample size was 179 which were selected purposively. The study showed that out of 179 respondents 89 (49.7%) were in the age groups of 30-39 years and the mean age of the respondents were 31.99 ± 6.01 years. A large number of respondents (55.9%) had monthly family income of Taka 10001-20000 and the mean family income was Taka 12776.54 ± 5230.13. Maximum respondents (73.7%) were Muslim, more than half (54.2%) were shift in charge, 39.1% of the respondents consisted of 4 family members, 43.6% respondents were accustomed to other type of eating habit and 38.5% respondents knew that malnutrition was the effect of lack of proper nutrition, 59.8% of the respondents knew that night blindness was the disease due to malnutrition, most of the respondents (91.6%) performed duties to maintain health, majority (62.0%) respondents used to do nothing to maintain healthcare for their children and 35.9% visited doctors single time in a month, 40.2% of the respondents told regular tooth brushing as type of healthy habits. Majority (64.8%) respondents used to brush twice a day, majority (50.8%) respondents used to wash hand after toileting, majority (62.08%) respondents used to bath daily, 43.0% and 31.8% of the respondents told that dysentery and diarrhea was due to eating without proper hand washing respectively. Majority (53.6%) respondents informed that they learned about personal hygiene from television, 45.8% respondents understood that use of safe water in every work as sanitation. Majority (50.84%) came from nuclear family; most (84.92%) had exercise habit and 40.22% had education level of class VIII. Most (75.42%) of the respondents had semi pucca houses and majority (69.83%) of the respondents used only water as materials for hand washing. This study provided some important information which might help the concerned authority to take appropriate measures to improve the health status of the workers.